2016
DOI: 10.1002/2016gl069638
|View full text |Cite
|
Sign up to set email alerts
|

Intensification of upwelling along Oman coast in a warming scenario

Abstract: The oceanic impact of poleward shift in monsoon low‐level jet (MLLJ) is examined using a Regional Ocean Modeling System (ROMS). Two sets of downscaling experiments were conducted using ROMS with boundary and initial conditions from six CMIP5 models. While outputs from the historical run (1981–2000) acts as forcing for the first, the second uses RCP8.5 (2080–2099). By comparing the outputs, it is found that Oman coast will experience an increase in upwelling in tune with MLLJ shift. Consistent with the changes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
30
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
2
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(32 citation statements)
references
References 39 publications
2
30
0
Order By: Relevance
“…However, we are aware that future and past monsoon changes generally come in complex spatial and temporal patterns, which may affect the projected OMZ response. For instance, a recent study by Praveen et al (2016) suggests that summer monsoon intensification will affect more the northern Arabian Sea (i.e., Sea of Oman) than its southern part (i.e., the Somali coast). This could alter the response of the OMZ depending on how the overall Arabian Sea productivity changes.…”
Section: Limitations Of the Idealized Wind Change Scenariosmentioning
confidence: 99%
See 2 more Smart Citations
“…However, we are aware that future and past monsoon changes generally come in complex spatial and temporal patterns, which may affect the projected OMZ response. For instance, a recent study by Praveen et al (2016) suggests that summer monsoon intensification will affect more the northern Arabian Sea (i.e., Sea of Oman) than its southern part (i.e., the Somali coast). This could alter the response of the OMZ depending on how the overall Arabian Sea productivity changes.…”
Section: Limitations Of the Idealized Wind Change Scenariosmentioning
confidence: 99%
“…This high productivity in conjunction with a sluggish circulation sustains the world's thickest OMZ, responsible for up to 40 % of global pelagic denitrification despite occupying less than 2 % of the World Ocean area (Bange et al, 2005). Future climate projections suggest that Indian summer monsoon may intensify in the future under a warmer climate (e.g., Wang et al, 2013;Sandeep and Ajayamohan, 2015;Praveen et al, 2016;deCastro et al, 2016). Praveen et al (2016) found that the future upwelling intensification will affect essentially the coast of Oman.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The future fate of upwelling, in the context of global warming, is a subject of debate. Several studies have argued that there will be intensification of coastal upwelling in response to the amplified landsea pressure gradient in the warming world (Bakun 1990;deCastro et al 2016;Praveen et al 2016). However, the story in the monsoonal Indian Ocean may be far more complex.…”
Section: Upwelling Coastal-open Interactionsmentioning
confidence: 99%
“…This high productivity in conjunction with a sluggish circulation sustains the world's thickest OMZ, responsible for up to 40 % of global pelagic denitrification despite occupying less than 2 % of the World Ocean area (Bange et al, 2005). Future climate projections suggest that Indian summer monsoon may intensify in the future under a warmer climate (e.g., Wang et al, 2013;Sandeep and Ajayamohan, 2015;Praveen et al, 2016;deCastro et al, 2016). Praveen et al (2016) found that the future upwelling intensification will affect essentially the coast of Oman.…”
Section: Introductionmentioning
confidence: 99%